Antyczne "Przemiany" i romantyczne metamorfozy. Tropami "Metamorfoz" Owidiusza w "Świteziance" Adama Mickiewicza - Klausa-Wartacz, Joanna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
The article is a new proposition in the field of philological research regarding connections between ancient and romantic literature. This paper presents an analysis of Mickiewicz’s ballad called Świtezianka as a text based on Ovid’s Metamorphoses.

The paper offers a new proposal of reading Ballads and romances of Adam Mickiewicz, and especially Świtezianka. It appears that Ovid was one of the most inspiring poets for Mickiewicz in his early writing period. On the other hand his ancient epos has always been an important point of reference for all great Polish poets. The ballad Świtezianka is constructed (interestingly enough), as a piece of epic literature with all its key elements: characters, events and background. Otherwise the author of this article focuses her attention on the concept of metamorphosis, as the most important structural point connecting the ancient text with its romantic counterpart. As we can see, both texts – Ovid’s epopee and Mickiewicz’s ballad – present similar stories about love and treachery, while using the same key elements of poetics.
Metamorphoses in both ancient and romantic literary traditions – following Ovid’s Metamorphoses in Mickiewicz’s Świtezianka
Keywords: Ovid; Mickiewicz Adam; 19th century; myth; metamorphosis; ballad; character; event; background